Evidentiranje medicinsko-tehničnih pripomočkov na kartici zdravstvenega zavarovanja - Bolka, Anka (Informatica Medica Slovenica, 2002)
For over a year now, the health insurance card has been a firmly established and accepted document. The Health Insurance Institute is continually enhancingthe system functionality, now through extensions of the card data set. This contribution depicts the goals and plan of a project aiming at registering of delivered medical technical aids on the card and the redressingof the current prescribing and delivering procedures.
Keywords: baze podatkov; Bolnik, identifikacijski sistemi; informacijski sistemi; Insurance, Health; Patient Identification Systems; Prescriptions, Non-Drug; Recepti, sanitetni pripomočki; Zavarovanje zdravstveno; zdravstvena kartica; zdravstveno zavarovanje; zdravstvo